Comments on the Influence of Canon Law on the Common Law Legal Tradition - Martínez-Torrón, Javier (Revue générale de droit, 1989)
In this paper, the author questions the conventional view that the civil law and common law traditions are radically different in their reception of Roman Law. He argues that Roman Law concepts, mediated by canon law, exerted a considerable influence over the common law. He identifies a number of channels through which this influence has shaped common law concepts. Thus, canonical equitas probably served as a model for the equitable rules bases on good faith. Although common law evolved in a distinctive way, because of procedural considerations, its evolutionary path had already been followed by that of canon law.